Efektivitas Konseling Virtual Berbasis Aplikasi Digital dalam Menumbuhkan Karakter Kristus Konseli Pada Aplikasi Virtual - Evi Sondang Pangaribuan (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
This study examines the effectiveness of virtual counseling based on digital applications in fostering Christlike character among Christian Education students and broader Christian counselees. Using a mixed - methods convergent design, quantitative data were collected from 42 active participants through Likert-scale questionnaires, complemented by qualitative interviews with selected counselors and counselees. The findings indicate a strong positive relationship between virtual counseling effectiveness and the growth of Christlike values, particularly love, humility, honesty, perseverance, and spiritual integrity. Key contributing factors include communication quality, counseling techniques, platform suitability, and counselee engagement. Despite technical and relational limitations inherent in virtual settings, digital counseling demonstrates significant potential as a pastoral and educational tool when grounded in biblical principles and relational sensitivity. This study affirms that digitally mediated counseling, when intentionally practiced, can serve as a meaningful instrument for spiritual formation in contemporary Christian education and ministry contexts, offering practical implications for counselors, educators, and faith-based institutions in integrating technology with holistic discipleship